Exposure to Yeast Shapes the Intestinal Bacterial Community Assembly in Zebrafish Larvae - Siriyappagouder, Prabhugouda; Galindo-Villegas, Jorge; Lokesh, Jep; Mulero, Victoriano; Fernandes, Jorge M. O.; Kiron, Viswanath (Frontiers in Microbiology, 2018)
Establishment of the early-life gut microbiota has a large influence on host development and succession of microbial composition in later life stages. The effect of commensal yeasts - which are known to create a conducive environment for beneficial bacteria - on the structure and diversity of fish gut microbiota still remains unexplored. The present study examined the intestinal bacterial community of zebrafish (Danio rerio) larvae exposed to two fish-derived yeasts by sequencing the V4 hypervariable region of bacterial 16S rRNA. The first stage of the experiment (until 7 days post-fertilization) was performed in cell culture flasks under sterile and conventional conditions for germ-free (GF) and conventionally raised (CR) larvae, respectively. The second phase was carried out under standard rearing conditions, for both groups. Exposure of GF and CR zebrafish larvae to one of the yeast species Debaryomyces or Pseudozyma affected the bacterial composition. Exposure to Debaryomyces resulted in a significantly higher abundance of core bacteria. The difference was mainly due to shifts in relative abundance of taxa belonging to the phylum Proteobacteria. In Debaryomyces-exposed CR larvae, the significantly enriched taxa included beneficial bacteria such as Pediococcus and Lactococcus (Firmicutes). Furthermore, most diversity indices of bacterial communities in yeast-exposed CR zebrafish were significantly altered compared to the control group. Such alterations were not evident in GF zebrafish. The water bacterial community was distinct from the intestinal microbiota of zebrafish larvae. Our findings indicate that early exposure to commensal yeast could cause differential bacterial assemblage, including the establishment of potentially beneficial bacteria.